2020
DOI: 10.21203/rs.3.rs-51257/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What interferes with conducting free lists? A comparative ethnobotanical experiment

Abstract: Background: The free list, also written “freelist”, or “free recall”, is an ethnographic method that characterizes the local knowledge of a population about a given cultural domain. However, there is still much to elucidate about the variables that can influence the number of items that participants cite using this technique. This study applied a casual-comparative experiemental design to analyze whether three months’ time, age and external stimuli influence the similarity of plant free lists applied at differ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Common ethnobotanical methods may not be culturally appropriate in Australian aboriginal research and this necessitates the development of alternative culturally sensitive study designs [37,57,58]. The use of tools such as free-listing were found to produce variable outcomes, even within a single participant (in separate interviews), or relating to age or the presence of a third party at the interview [219]. Similarly, a Bolivian study found that even subtle changes in the use of methods of free-listing and semi-structured interviews can produce markedly different results [220].…”
Section: Discussion On Ethnobiology Of C Spinarummentioning
confidence: 99%
“…Common ethnobotanical methods may not be culturally appropriate in Australian aboriginal research and this necessitates the development of alternative culturally sensitive study designs [37,57,58]. The use of tools such as free-listing were found to produce variable outcomes, even within a single participant (in separate interviews), or relating to age or the presence of a third party at the interview [219]. Similarly, a Bolivian study found that even subtle changes in the use of methods of free-listing and semi-structured interviews can produce markedly different results [220].…”
Section: Discussion On Ethnobiology Of C Spinarummentioning
confidence: 99%
“…In addition, the LKMP recovered from the six communities studied may not represent the full knowledge of an individual since participants may not express all of their LKMP for not remembering it or feeling shy to do it during the interview. The partial communication of LKMP by the participants may result from the influence of different factors, such as the presence of third parties during the interview, and/or social factors like the interviewee's age, as reported by Meireles, Albuquerque, and Medeiros (2021). One way to circumvent such influences would be to perform annual repetitions of the survey in the area.…”
Section: Discussionmentioning
confidence: 99%